Can benthic foraminifera be used as bio-indicators of pollution in areas with a wide range of physicochemical variability?. (5th December 2016) - Martins, Maria Virgínia Alves; Pinto, Anita Fernandes Souza; Frontalini, Fabrizio; da Fonseca, Maria Clara Machado; Terroso, Denise Lara; Laut, Lazaro Luiz Mattos; Zaaboub, Noureddine; da Conceição Rodrigues, Maria Antonieta; Rocha, Fernando
Abstract: The Ria de Aveiro, a lagoon located in the NW coast of Portugal, presents a wide range of changes to the natural hydrodynamical and physicochemical conditions induced for instance by works of port engineering and pollution. In order to evaluate the response of living benthic foraminifera to the fluctuations in physicochemical parameters and pollution (metals and TOC), eight sediment samples were collected from canals and salt pans within the Aveiro City, in four different sampling events. During the sampling events, salinity showed the most significant fluctuations among the physicochemical parameters with the maximum range of variation at Troncalhada and Santiago salt pans. Species such as Haynesina germanica, Trochammina inflata and Entzia macrescens were found inhabiting these hypersaline environments with the widest fluctuations of physicochemical parameters. In contrast, Ammonia tepida dominated zones with high concentrations of metals and organic matter and in lower salinity waters. Parameters related to benthic foraminiferal assemblages (i.e., diversity and evenness) were found to significantly decline in stations polluted by metals and characterized by higher TOC content. Foraminiferal density reduced significantly in locations with a wide range of physicochemical temporal variability. This work shows that, even under extreme conditions caused by highly variable physicochemical parameters, benthic foraminiferal assemblages might be used as valuable bioindicators of environmental stress. Highlights: Human impact in the coastal lagoon of Aveiro. Living benthic foraminifera in canals and salt pans of Aveiro city. Foraminifera used as biological indicators of pollution. Seasonal and spatial changes of physicochemical parameters and pollution.